2021
DOI: 10.3389/fpsyg.2021.740221
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perceptual Load Attenuates Age-Related Audiovisual Integration in an Audiovisual Discrimination Task

Abstract: Previous studies confirmed that the cognitive resources are limited for each person, and perceptual load affects the detection of stimulus greatly; however, how the visual perceptual load influences audiovisual integration (AVI) is still unclear. Here, 20 older and 20 younger adults were recruited to perform an auditory/visual discrimination task under various visual perceptual-load conditions. The analysis for the response times revealed a significantly faster response to the audiovisual stimulus than to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recent studies have found that visual attentional load reduces the audiovisual integration effect, and that the audiovisual integration effect increases in older adults but is delayed. In addition, a shift in AVI oscillation from anterior to posterior regions in older adults is an adaptive mechanism (Ren et al, 2020(Ren et al, , 2021b. Researchers have also explored the effect of auditory attentional load on audiovisual integration from a behavioral perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that visual attentional load reduces the audiovisual integration effect, and that the audiovisual integration effect increases in older adults but is delayed. In addition, a shift in AVI oscillation from anterior to posterior regions in older adults is an adaptive mechanism (Ren et al, 2020(Ren et al, , 2021b. Researchers have also explored the effect of auditory attentional load on audiovisual integration from a behavioral perspective.…”
Section: Introductionmentioning
confidence: 99%